THE ANALYSIS OF STATE DEFENSE STRATEGY IN THE SEA OF THE MALAYSIA STATE IN ORDER TO FACE THE THREAT IN THE INDO-PACIFIC REGION - Yos Aru Moreta; Okol Sri Suharyo; Joko Purnomo; Hadi Mardiyanto (STTAL POSTGRADUATE - INTERNATIONAL CONFERENCE, 2024)
Malaysia, as a strategic country in the Indo-Pacific region, faces various complex maritime security challenges. In maintaining its sovereignty, Malaysia must manage threats arising from overlapping territorial claims in the South China Sea, piracy and maritime crime in the Malacca Strait, as well as geopolitical tensions between major powers such as the United States and China. Malaysia's centralized federal structure gives the federal government the authority to determine national strategic policy, including international cooperation and maritime defense. This research aims to analyze Malaysia's maritime defense strategy in facing threats in the Indo-Pacific region using game theory, maritime strategy theory, and collective security theory. This research identifies several strategies that Malaysia can take, including carrying out bilateral military exercises, joint patrols, exchanges of officers and students, as well as sharing technology and defense industry cooperation with neighboring countries such as Indonesia. Through game theory analysis, it was found that the optimal strategy for Malaysia is to carry out joint operations around the Malacca Strait and the waters bordering Indonesia, which will increase maritime security and prevent illegal activities. The research results show that a combination of bilateral military exercises and joint patrols, supported by personnel exchange programs and technological collaboration, is the most effective strategy to increase Malaysia's maritime defense capabilities. Implementation of these strategies not only strengthens diplomatic relations and synergy in developing human resources and defense technology but also creates stronger stability and security in the Indo-Pacific region. The recommendation from this research is that Malaysia and Indonesia actively implement the strategies that have been identified and continue to evaluate and adjust to ensure the sustainability and increased effectiveness of maritime defense and security cooperation in the region.